Enhanced Li+ Transport in Ionic Liquid‐Based Electrolytes Aided by Fluorinated Ethers for Highly Efficient Lithium Metal Batteries with Improved Rate Capability. Issue 7 (6th June 2021) - Liu, Xu; Zarrabeitia, Maider; Mariani, Alessandro; Gao, Xinpei; Schütz, Hanno Maria; Fang, Shan; Bizien, Thomas; Elia, Giuseppe Antonio; Passerini, Stefano
Abstract: FSI − ‐based ionic liquids (ILs) are promising electrolyte candidates for long‐life and safe lithium metal batteries (LMBs). However, their practical application is hindered by sluggish Li + transport at room temperature. Herein, it is shown that additions of bis(2, 2, 2‐trifluoroethyl) ether (BTFE) to LiFSI‐Pyr14 FSI ILs can effectively mitigate this shortcoming, while maintaining ILs′ high compatibility with lithium metal. Raman spectroscopy and small‐angle X‐ray scattering indicate that the promoted Li + transport in the optimized electrolyte, [LiFSI]3 [Pyr14 FSI]4 [BTFE]4 (Li3 Py4 BT4 ), originates from the reduced solution viscosity and increased formation of Li + ‐FSI − complexes, which are associated with the low viscosity and non‐coordinating character of BTFE. As a result, Li/LiFePO4 (LFP) cells using Li3 Py4 BT4 electrolyte reach 150 mAh g −1 at 1 C rate (1 mA cm −2 ) and a capacity retention of 94.6% after 400 cycles, revealing better characteristics with respect to the cells employing the LiFSI‐Pyr14 FSI (operate only a few cycles) and commercial carbonate (80% retention after only 218 cycles) electrolytes. A wide operating temperature (from −10 to 40 °C) of the Li/Li3 Py4 BT4 /LFP cells and a good compatibility of Li3 Py4 BT4 with LiNi0.5 Mn0.3 Co0.2 O2 (NMC532) are demonstrated also. The insight into the enhanced Li + transport and solid electrolyte interphase characteristics suggests valuable information to develop IL‐based electrolytes for LMBs. Abstract : Fluorinated ethers with low viscosity and non‐solvating character effectively promote the Li + transport of ionic liquid (IL)‐based electrolytes, meanwhile maintaining a high compatibility with the lithium metal anode. The insight of the unique ion–ion interaction, solution structure, and solid electrolyte interphase provides valuable information for the design of IL‐based electrolytes for lithium metal batteries.